Samuel Adams: America's Revolutionary Politician - Alexander, John K. (Rowman & Littlefield Publishers, 2004)
Samuel Adams: America's Revolutionary Politician offers a fresh full-life biography of the man Thomas Jefferson once described as the helmsman of the American Revolution. In his study, historian John K. Alexander uses narrative history to argue that Samuel Adams was both America's first professional politician and its first modern politician. Adams, Alexander argues, was an unwavering politician who strove to protect the people's basic rights and who emphasized the importance of virtue, liberty, a sense of duty, and education in fashioning a republican society. John K. Alexander's fresh reading of Adams's record, and a uniquely close look into his personal life, uncovers a masterful politician and a man consistent in his beliefs.